Osteoprotegerin, s-RANKL, and selected interleukins in the pathology of bone metabolism in patients with Crohn’s disease - Krela-Kaźmierczak, Iwona; Wysocka, Ewa; Szymczak, Aleksandra; Eder, Piotr; Michalak, Michał; Łykowska-Szuber, Liliana; Stawczyk-Eder, Kamila; Klimczak, Katarzyna; Linke, Krzysztof; Horst-Sikorska, Wanda (Gastroenterology Review/Przegląd Gastroenterologiczny, 2016)
Introduction : Crohn’s disease (CD) promotes the development of osteopaenia/osteoporosis, the cytokine background of which is not fully known. Aim : Evaluation of bone mineral density (BMD), the prevalence of osteopaenia and osteoporosis, and the determination of the levels of selected interleukins (IL), osteoprotegerin (OPG), and s-RANKL proteins in patients with CD in relation to a control group and assessment of the relationship between the tested cytokines, OPG, s-RANKL, and BMD. Material and methods: Thirty-seven CD patients and 37 healthy volunteers (control group) were enrolled into the study. Densitometry of the lumbar spine (L2–L4) and of the femoral neck using the DXA technique was carried out. Serum levels of: IL-13, IL-4, IL-17, IL-1, OPG, and s-RANKL were determined using the ELISA method. Progression-of-disease questionnaires were collected. Results : The prevalence of osteoporosis and osteopaenia in the CD group was: 18.92% and 32.43% in L2–L4; 13.51% and 35.13% in the neck, respectively. The IL-13 and IL-1 concentrations were significantly higher and OPG was significantly lower in CD patients when compared to controls. In the case of all subjects: IL-13 correlated negatively with the BMD of the neck, IL-17 correlated negatively with the Z-score of L2–L4, and OPG correlated negatively with the IL-13. In the case of CD patients, IL-4 correlated negatively with the BMD of L2–L4. Conclusions : The incidence of osteopaenia and osteoporosis in Polish CD patients is high. IL-13, IL-1, and IL-4 seem to be connected with the pathology of decreased BMD in CD. It can be hypothesised that IL-13 may lower BMD by modulating OPG.